Political violence and the police in India - Subramanian, K. S. (SAGE Publications, 2007)
Political violence and state response in India -- The Indian police system in crisis -- Intelligence bureau: an instrument of partisan politics -- Central paramilitary forces: A parallel police force? -- Naxalite violence: What can the Union Home Ministry do? -- Violence against Dalits and Adivasis: Whither social justice? -- State-sponsored violence against the Muslims in Gujarat, 2002: a case study in police partisanship -- Political violence in the northeast: the human rights of ordinary people